Factors influencing the adoption of sustainable rice farming practices in Khyber Pakhtunkhwa, Pakistan - Zakir Ullah; Jiqin Han; Aftab Anwar; Ahmad Sajjad (PLoS ONE, 2026)
Rice is a major staple crop and an important source of income for rural households in Pakistan. Its production in Khyber Pakhtunkhwa (KPK) is challenged by rising input costs, climate variability, and limited institutional support, which undermine productivity and long-term sustainability. Sustainable farming practices (SFPs) offer opportunities to improve resource efficiency and farm profitability. This study identifies the key factors that influence the adoption of SFPs among rice farmers in KPK and evaluates their economic impacts. Primary data were collected from 283 rice-growing households in Khyber Pakhtunkhwa, Pakistan, between 18 th January 2025 and 27 th April 2025 using multistage random sampling. Adoption patterns of practices such as crop rotation and intercropping, reduced chemical use, natural fertilizers, and water-saving methods were examined using descriptive statistics, chi-square testing, cost–benefit analysis, logistic regression, propensity score matching, structural equation modeling, and a decision-tree model. Results show that 56.2 percent of farmers adopted at least one sustainable practice. Education, farm size, access to credit and subsidies, market proximity, and participation in training significantly increased the likelihood of adoption. Adopters achieved higher yields (about 430 kg/ha more) and greater profitability than non-adopters (P < 0.01). Cost–benefit analysis confirmed stronger benefit-cost ratios for sustainable systems. Propensity score matching further supported positive effects on profitability, yield, and household income. The findings highlight the economic viability of SFPs in smallholder rice systems. Wider adoption will require expanded farmer training, improved access to concessional credit and subsidies, and stronger extension support. Promoting these practices can raise farm incomes, improve resource use, and support climate-resilient rice production in KPK, Pakistan.